The illusionist [videorecording (DVD)] - MacNeil, Duncan, 1920-1996-; Rankin, Eilidh; Donda, Jean-Claude; Mearns, Raymond (Sony Pictures Home Entertainment, 2011)
A French illusionist finds himself out of work and travels to Scotland. While performing in a village pub, he encounters Alice, an innocent young girl, who will change his life forever.